Strengthening Supervision Of Madrasah Based On Management In Rural - Tubagus Syihabudin; Encep Syarifudin; Eneng Muslihah (At-Tarbiyat, 2023)
Supervision is a management instrument that needs attention; on this basis, the management function is improving. Madrasahs are an important part of the national education system with distinctive characteristics but are still weak in the oversight function in management. Madrasah-Based Management (MBM) is the autonomy given to madrasas to regulate all existing policies in their environment in order to achieve madrasa goals mandated by the Ministry of Religion. In practice, madrasas are given full authority to regulate learning curriculum management, student management, infrastructure management, personnel management, financial management, public relations management, and special services management. This study aimed to explore strengthening the supervision of madrasah-based management at the State Aliyah Madrasah in rural areas. This research uses qualitative methods with a case study approach. The research location is at Madrasah Aliyah Negeri 2 Serang. They are collecting data using interviews and observation, and literature study. Data validity used triangulation techniques, while analysis used narrative techniques. The results show that the supervisory function of madrasah-based management includes weak team performance, limited infrastructure, curriculum, funding and teacher ranks. The research implies that the stronger supervision of madrasah-based management in rural areas will improve the quality of madrasah.